2020
DOI: 10.47492/jih.v9i2.292
|View full text |Cite
|
Sign up to set email alerts
|

Attractive, Active, Interactive, and Communicative. Model Pelatihan Bahasa Inggris Hospitality Pada Mahasiswa Diploma Tiga Program Studi Perjalanan Wisata Sekolah Tinggi Pariwisata Mataram

Abstract: Tujuan utama pembelajaran adalah untuk dapat mengembangkan potensi yang dimiliki mahasiswa dengan baik, untuk mencapai kualitas yang diinginkan perlu adanya berbagai inovasi dalam proses pembelajaran, tenaga pendidik dituntut mampu memilih metode dan media pembelajaran yang tepat. Selain itu kemampuan literasi juga diperlukan dalam proses pembelajaran sehingga nantinya dapat meningkatkan minat belajar mahasiswa dan memudahkannya dalam memahami materi pembelajaran. Namun, realitanya dalam proses pembelajaran sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Nikoopour and Farsani (2011) highly suggested that the learners learned the materials they needed. Learning materials which were relevant to the expected work field would motivate the students to speak more bravely in the classroom, increase their English proficiency and support their carrer development (Gadu & Mahsun, 2018). A strong relation between the English materials being studied and the field of study the learners are majoring would enable the learning outcomes of the course were on the correct track.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nikoopour and Farsani (2011) highly suggested that the learners learned the materials they needed. Learning materials which were relevant to the expected work field would motivate the students to speak more bravely in the classroom, increase their English proficiency and support their carrer development (Gadu & Mahsun, 2018). A strong relation between the English materials being studied and the field of study the learners are majoring would enable the learning outcomes of the course were on the correct track.…”
Section: Discussionmentioning
confidence: 99%
“…These scopes were proven to be contributive to improve the quality and the success of an ELT classroom as shown in some research findings, i.e. perception (Iftanti & Maunah, 2021;Yuntao, 2019;Badiozaman, Leong & Jikus, 2019;Emiliasari & Kosmajadi, 2019;Budianto, 2019), expectation (Loveta, Loeneto, & Vianty, 2020;Eriani, Pratolo, Nailufer & Astuti, 2019;Gadu & Mahsun, 2018), perception and expectation (Halim, et. al, 2021), difficulties (Hajar & Rahman, 2022;Ngoc & Mai, 2020: Patau, 2018.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Suatu proses pembelajaran bisa dikatakan efektif jika berhasil membawa siswa untuk mencapai tujuan pembelajaran yang sudah dirancang, menyajikan suasana pembelajaran yang menarik dan melibatkan siswa secara aktif, sehingga menunjang pencapaian tujuan pembelajaran (Asmara & Nindianti, 2019). Pembelajaran dinyatakan efektif jika pencapaian tujuan instruksional yang telah dirumuskan dalam pembelajaran dapat terlaksana secara maksimal (Gadu & Bagiastra, 2003). Efektivitas metode, model, pendekatan, dan strategi pembelajaran menjadi tolok ukur kesuksesan dari sebuah rangkaian pembelajaran yang dilakukan.…”
Section: Pendahuluanunclassified
“…Therefore, English education is very important to prepare students and individuals for success in the current era of globalization. In learning English, it is important to understand grammar and language structure as well as the ability to speak, write, read and listen effectively and efficiently (Gadu & Bagiastra, 2003).…”
Section: Introductionmentioning
confidence: 99%